Distribution and shape analysis of Phorcus lineatus and Phorcus sauciatus along the Portuguese coast - Costa, Margarida Antunes da (2015)
Tese de mestrado em Ecologia Marinha, apresentada à Universidade de Lisboa, através da Faculdade de Ciências, 2015